2011
DOI: 10.1259/bjr/51830082
|View full text |Cite
|
Sign up to set email alerts
|

Variant ventral intrahepatic course of inferior vena cava: volume-rendering and maximum intensity projection CT findings

Abstract: ABSTRACT. Anatomically, the inferior vena cava (IVC) courses through the liver posteriorly and drains into the right atrium. We describe an extremely rare case of the anterior intrahepatic course of the IVC that drained into the right atrium seen on a CT scan of a healthy 26-year-old female who presented to the emergency room with abdominal pain. The anterior intrahepatic segment was bridged to the posteroinferior portion of the IVC by an oblique segment. Associated renal and arterial anomalies were also obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…In the presented case, family history was remarkable for essential HT and premature coronary heart diseases, but not for any vascular abnormalities. In addition, no defects of the heart were found in the subject; however some types of the IVC malformations were described in patients with congenital cardiac anomalies [1]. We also did not detect any serious renal anomalies, except for a cyst (17 mm) in the right kidney, whereas Gayer et al [4] reported right renal aplasia or hypoplasia in a small series of patients with IVC anomalies.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In the presented case, family history was remarkable for essential HT and premature coronary heart diseases, but not for any vascular abnormalities. In addition, no defects of the heart were found in the subject; however some types of the IVC malformations were described in patients with congenital cardiac anomalies [1]. We also did not detect any serious renal anomalies, except for a cyst (17 mm) in the right kidney, whereas Gayer et al [4] reported right renal aplasia or hypoplasia in a small series of patients with IVC anomalies.…”
Section: Discussioncontrasting
confidence: 41%
“…In general, it is mostly incidentally diagnosed during surgeries, or through imaging of the area, usually with CT scanning or MRI done for other reasons [1,2]. If a venous collateral circulation is efficient enough, this anomaly is usually asymptomatic [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Embryologically, the normal IVC is composed of four segments: hepatic, suprarenal, renal and infrarenal [1].…”
Section: Discussionmentioning
confidence: 99%
“…& Zuhal Gülşen sayinerzuhal@yahoo.com.tr1 Department of Radiology, Ankara Education and Training Hospital, Altindag, Ankara, Turkey…”
mentioning
confidence: 99%
“…Useful clinical applications of the VR technique for visualizing complex anatomy and pathology have been described in many radiological fields and include otorhinolaryngiology [9], neurosurgery and cranio-facial surgery [10], female imaging [1], vascular anomalies and variants [11, 12], and coronary artery anatomy and anomalies [1315]. …”
Section: Volume Rendering – Potential Clinical Applicationsmentioning
confidence: 99%